2015
DOI: 10.1021/jacs.5b09790
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Gas–Water–Solid Interface for Multiphase Catalysis

Abstract: Despite their wide utility in laboratory synthesis and industrial fabrication, gas-water-solid multiphase catalysis reactions often suffer from low reaction efficiency because of the low solubility of gases in water. Using a surface-modification protocol, interface-active silica nanoparticles were synthesized. Such nanoparticles can assemble at the gas-water interface, stabilizing micrometer-sized gas bubbles in water, and disassemble by tuning of the aqueous phase pH. The ability to stabilize gas microbubbles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 62 publications
2
88
0
1
Order By: Relevance
“…The measurements revealed that the zeta potential values at pH 5 and pH 7 were positive, which meant that negative ions could approach the positive ions on the surface of the pH-SiNPs because of the protonation of the amino groups on the pH-SiNPs 39 . However, the zeta potential value decreased to nearly −28 mV at pH 9, indicating that few negative ions attached to the surface of the pH-SiNPs 39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The measurements revealed that the zeta potential values at pH 5 and pH 7 were positive, which meant that negative ions could approach the positive ions on the surface of the pH-SiNPs because of the protonation of the amino groups on the pH-SiNPs 39 . However, the zeta potential value decreased to nearly −28 mV at pH 9, indicating that few negative ions attached to the surface of the pH-SiNPs 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The highest peak at a binding energy of 532.0 eV corresponding to the O1 s peak illustrated the presence of abundant Si-O-Si group formed by the reaction of the organosilanes with the silica nanoparticles. A peak at approximately 103.6 eV, which is the Si2 p peak of SiO 2 , showed that there was little bare space on the silica nanoparticles 14,39 . These facts demonstrated that organosilanes were successfully grafted on the surface of the silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control of Pickering emulsions plays a pivotal part in many significant processes, for example, oil extraction and recovery [29,30], emulsion polymerization [31,32,33,34], and heterogeneous catalysis [35,36,37]. In this regard, many endeavors have been made in developing controllable Pickering emulsions.…”
Section: Introductionmentioning
confidence: 99%